2011
DOI: 10.1007/s10725-011-9609-7
|View full text |Cite
|
Sign up to set email alerts
|

Two calcium dependent protein kinases are differently regulated by light and have different activity patterns during seedling growth in Pharbitis nil

Abstract: In this study using biochemical approaches we identified two calcium-dependent protein kinases (CDPKs) named PnCDPK52 and PnCDPK56 in soluble protein extracts from seedlings of Pharbitis nil. Both enzymes phosphorylated the specific substrate histone III-S in the presence of Ca 2? and cross-reacted with antibodies against the CDPK. PnCDPKs exhibited quite different activity and protein levels during germination and successive stages of seedling growth. PnCDPK52 protein level was high in seeds and during germin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Calcium ions are the major second messenger in plants, and the calcium signaling pathway has been extensively studied [ 47 , 48 ]. Recent studies have shown that CaCl 2 (calcium chloride) can promote the induction of embryogenic calli (EC) and the germination of somatic embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium ions are the major second messenger in plants, and the calcium signaling pathway has been extensively studied [ 47 , 48 ]. Recent studies have shown that CaCl 2 (calcium chloride) can promote the induction of embryogenic calli (EC) and the germination of somatic embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium-dependent cellular processes are regulated through intracellular Ca 2+ -binding proteins, of which the best-studied are calmodulin (CaM), calmodulin-like proteins (CMLs) and calcium-dependent protein kinases (CDPKs). These proteins bind Ca 2+ ions through the EF hand motif, a conserved helix-loop-helix structure that binds a single Ca 2+ ion, thereby causing a change in the conformation that, in turn, can activate target proteins or cause self-activation [31][32][33][34]. Since it was reported that CaM/Ca 2+ affects the activity of group I animal PDEs and the PDE domain of the ATKUP5 [17,35] and that a protein sequence analysis revealed that BDPDE1 also contains a predicted CaM-binding site between amino acids 50 and 70, we investigated the possible interactions of CaM and CaM-like isoforms with plant PDE using fluorescence spectroscopy.…”
Section: The Calmodulin/ca 2+ Complex Stimulates Bdpde1 Activitymentioning
confidence: 99%
“…In the next step, we ignore the needs of all species of fauna and flora, we design lighting systems adjusted to our eyesight. Finally, we are surprised why some animal species die in automobile accidents [1], birds die after crashing into skyscrapers [2,3] and the greenhouse plants grow slower [4][5][6] than we expect? After all, we provided white light with a high colour rendering index or selectable colour temperature -but in pursuit of economic efficiency, we have forgotten about nature.…”
mentioning
confidence: 99%